Stator Harmonic Optimal Control of Permanent Magnet Synchronous Motor in Electric Vehicle - WANG Shuo; WANG Xu-dong; JIN Ning-zhi; LIU Yu-bo; XIE Rui (Journal of Harbin University of Science and Technology)
For the problem of harmonics in the motor stator current under the traditional control strategy of the permanent magnet synchronous motor ( PMSM) ，an improved control method of suppressing current distortion by voltage compensation is proposed. Under the premise of the traditional dual feedback control frame，the high-order harmonic component is extracted and the harmonic feedback is added to realize the optimization of the stator current，the torque ripple is restrained and the smoothness of electric vehicle running is improved. By analyzing the high harmonic current waveform and torque waveform under the Matlab / Simulink environment simulation experiment，confirmed that the method significantly inhibited the motor stator current harmonics and validate the effectiveness of the proposed control algorithm．